Perancangan Sistem Transfer Daya Nirkabel untuk Unmanned Aerial vehicle (UAV) Micro Jenis Quadcopter - Pratomo, Setyawan Wahyu (JURNAL NASIONAL TEKNIK ELEKTRO, 2016)
In the Unmanned Aerial Vehicle ( UAV ) type of Quadcopter,  the source of  power supply in form of a battery that is only able to work 10-15 minutes in the air is a own  issue for the performance of Quadcopter. While the performance of quadcopter  at a high that are difficult to reach, it is expected over the role an  operator must manually connect the charging cable  to battery can be replaced by the system automatically when battery runs out. For that, in this paper discusses design of wireless power transfer system for  Quadcopter  to charge battery without the help of  an  operator and not to be done  landfalls  on the ground. The  recharging process of  battery can be done at the top of the building or in the common  ground  that  has  been installed wireless power transfer. The aim is to improve the performance of  quadcopter`s work  in the air in accordance with the usefullness. From the design of wireless power transfer system for quadcopter`s charging the battery obtained the results the best efficiency power transfer is 62.24 % with effective distance 10cm.  The frequency`s system obtained from an Oscillator Colpitss 333,1KHz by implementing the principles of electromagnetic induction.Keywords : Quadcopter, charging battery,electromagnetic inductionAbstrak— Dalam Unmanned Aerial Vehicle ( UAV ) jenis Quadcopter, sumber catu daya berupa baterai yang hanya mampu bekerja 10-15 menit di udara merupakan permasalahan tersendiri bagi performa Quadcopter. Sedangkan perfomansi dari Quadcopter pada ketinggian yang susah dijangkau, diharapkan peran operator  yang  selama ini harus mengkoneksikan secara manual kabel charging ke baterai bisa digantikan oleh sistem secara otomatis ketika baterai akan habis. Untuk itu dalam  paper ini membahas  suatu perancangan sistem transfer daya nirkabel untuk  Quadcopter  mengisi ulang  baterai  tanpa bantuan operator  dan tidak harus dilakukan pendaratan di  atas tanah.  Proses isi ulang ( charging ) baterai  bisa dilakukan di atas gedung maupun  di landasan yang telah terpasang transfer daya nirkabel. Tujuannya adalah meningkatkan performansi kerja Quadcopter di udara sesuai dengan kegunaanya.  Dari perancangan sistem transfer daya nirkabel untuk  Unmanned Aerial Vehicle ( UAV ) jenis Quadcopter  mengisi ulang ( charging ) baterai, diperoleh hasil efisiensi transfer daya terbaik sebesar  62,24% dengan jarak efektif 10 cm.  Frekuensi sistem transfer daya nirkabel  diperoleh dari rangkaian Colpitss Oscillator sebesar 333,1 KHz dengan menerapkan prinsip induksi elektromagnetik.Kata Kunci : Quadcopter, charging baterai, induksi elektromagnetik